Vertical distribution and seasonal dynamics of the populations of the macrozoobenthos from Lake Prespa - Angelovski, Petar; Šapkarev, Jonče; Karaman, Biljana; Smiljkov, Stoe (Macedonian Journal of Ecology and Environment, 1995)
Of the all natural great lakes, the macrozoobenthos of Lake Prespa has been investigated at least. The bottom fauna of the transect Stenje -Krani beginning at village Stenje ending at 20m depth was subject to over recent investigations. The structure of this fauna, vertical distribution of all present animal groups and of all identified species as well as their density of populations were studied. The seasonal changes of the animals during 1992 and their population density, constancy and abundance have been investigated as well.